Diseño de un mapa estratégico de afectación y dispersión acústica, mediante el monitoreo de ruido ambiental, para la identificación y medición de fuentes emisoras, en el centro histórico de la ciudad de Latacunga, periodo 2015 - Ronquillo Cando, Margarita Alexandra (2015)
The present investigative work has as objective to design a strategic map of noise in the Historical Center of Latacunga city, with the purpose to evaluate and to announce the acoustic situation of the colonial area of the city, allowing to know the levels of environmental noise, its dispersion inside the study area and therefore the identification of affected and calm areas. To carry out this study it was took into account some aspects and processes attached to national and international environmental standards and the placement of helpful convenient methods and techniques, also details according to the experience gained. Coming off from the acoustic monitoring program, established for the study area, the location map of monitoring points, which results will be reflected in the strategic map of acoustically affected areas in the Historic Center of the city of Latacunga ....